KEUDUDUKAN PPAT DALAM PELAKSANAAN HAK TANGGUNGAN SECARA ELEKTRONIK DALAM HUKUM POSITIF INDONESIA - Harniwati Harniwati (Ensiklopedia of Journal, 2021)
PPAT in carrying out his position must be careful. As an official whose signature is capable of causing a transfer of rights, it is only natural that the PPAT act prudently in carrying out the duties of his position. Because every form of authority is given by law, there is also legal responsibility. There will be no authority that is not accompanied by legal responsibility. In addition to the installation of electronic Mortgages raises legal responsibility, the process of installing electronic Mortgages also raises obstacles. A very influential constraint is the internet network. This is because the process of installing Mortgage Rights is already electronic, so of course this will depend on the internet network itself. The process of validation, checking certificates, and registration of Mortgage are very dependent on good internet quality. The validation process is carried out by the Land Office, if the internet network is bad, it will take more time in the validation process. During the process of moving until the internet network is installed at the new Land Office, certificate validation services cannot be performed. Then this also has an impact on certificate checking services by PPAT and electronic Mortgage registration, because the network on the Partner Application is directly connected to the internet network at the Land Office. So that PPAT in the installation of electronic Mortgage, is not only faced with its responsibilities in carrying out the position but also must be ready to face the existing obstacles, especially obstacles in the installation of electronic Mortgage.Keywords: PPAT, Mortgage, Electronic.